Investigating the Effects of Employee Knowledge Sharing Behaviors on Innovation in Services and Processes in Selected Sports Federations - Shahab Bahrami; Mahtab Moshtaghi; Maryam Rok Rok (بازیابی دانش و نظام‌های معنایی, 2018)
Purpose: The purpose of this study was to investigate the relationship between knowledge sharing practices and innovation in services and processes in selected sports federations of the Islamic Republic of Iran. Methodology: The research data were collected using a questionnaire from 110 employees working in these three federations. Data were analyzed with descriptive, inferential and structural equation modeling methods using SPSS and SmartPLS software. Results: The results of the study showed that the status of the variables of knowledge sharing and innovation in services and processes are higher than average. Also, the results of structural equation modeling showed that knowledge sharing behaviors have a positive effect on innovation in services and innovation in processes. Conclusion: In order to improve knowledge sharing in sports federations, it is necessary to promote innovation in services and processes. In other words, innovation in services and processes lays a foundation for improving knowledge sharing practices.